Parameters affecting Tractor Fuel Consumption during Primary Tillage Operation in Uyo, Akwa Ibom State, Nigeria - Okoko, P.; Olosunde, W. A. (International Journal of Environment, Agriculture and Biotechnology, 2023)
Tractor fuel consumption is a vital parameter in management of farm machinery. Parameters affecting tractor fuel consumption in litres per hectare(L/ha) during ploughing operation in Uyo was investigated. The study was conducted at the University of Uyo teaching and research farm, Uyo in Akwa Ibom State, Nigeria. The soil in the study location was characterized as clay loam. Effects of operation parameters on fuel consumption for ploughing operation were investigated using One-Way Repeated Measures Analysis of Variance. The findings of the study indicate that at ˂0.05 significance level, operation parameters had significant effect on tractor fuel consumption during ploughing operation. The study had identified factors affecting tractor fuel operation during ploughing operation in the study location.